Analysis of 24 years of mesopause region OH rotational temperature observations at Davis, Antarctica – Part 1: Long-term trends - French, W. John R.; Mulligan, Frank J.; Klekociuk, Andrew R. (2020)
The long term trend, solar cycle response and residual variability in 24 years of hydroxyl nightglow rotational temperatures above Davis Research Station, Antarctica (68° S, 78° E) is reported. Hydroxyl rotational temperatures are a layer-weighted proxy for kinetic temperatures near 87 km altitude and have been used for many decades to monitor trends in the mesopause region in response to increasing greenhouse gas emissions. Routine observations of the OH(6–2) band P-branch emission lines using a scanning spectrometer at Davis station have been made continuously over each winter season since 1995. Significant outcomes of this most recent analysis update are (a) a record low winter-average temperature of 198.3 K is obtained for 2018 (1.7 K below previous low in 2009) (b) a long term cooling trend of 1.2 K/decade persists, coupled with a solar cycle response of 4.3 K/100 solar flux units and (c) we find evidence in the residual winter mean temperatures of an oscillation on a quasi-quadrennial (QQO) timescale which is investigated in detail in part 2 of this work. Our observations and trend analyses are compared with satellite measurements from Aura/MLS version v4.2 level 2 data over the last 14 years and we find close agreement (a best fit) with the 0.00464 hPa pressure level values. The solar cycle response, long-term trend and underlying QQO residuals are consistent with the Davis observations. Consequently, we extend the Aura/MLS trend analysis to provide a global view of solar response and long term trend for southern and northern hemisphere winter season to compare with other observers and models.